Influencing factors of high school seat selection and relationship with students' academic performance - Mohammad Moslemi Haghighi, 1978-; Mahmud Mohd. Jusan; Fakulti Alam Bina (2014)
Thesis (Ph.D (Senibina)) - Universiti Teknologi Malaysia, 2014